Comenius : l’université, un atelier de l’humanité ? - Martin Strouhal; Magdalena Kohout-Diaz (Éducation et Socialisation)
This essay is a critical reflection on the paradoxes of contemporary university education. On the one hand, it highlights the ideals of democratisation of education and accessibility for all, as well as the valorisation of education in an increasingly open and inclusive society. On the other hand, it mentions the increased development of discrimination, symbolic violence, and inequalities linked to certain aspects of so-called mass education, such as excessive attachment to status prerogatives (entitlement). The tendency to view university teaching as a managerial activity, limited to concrete and practical objectives, to the detriment of a conception of education as a form of humanity, is not without long-term consequences. Education can only flourish if it is seen as a real workshop for humanity, in the words of Comenius himself. At the very least, we believe it is necessary to think carefully about the aims of university education, beyond its managerial aspects and practical objectives, and to emphasise its essential link with the development of humanity.